Localization of prion-destabilizing mutations in the N-terminal non-prion domain of Rnq1 in Saccharomyces cerevisiae - Shibata, Shoichiro (Landes Bioscience, 2009)
[PIN(+)] is the prion form of Rnq1 in Saccharomyces cerevisiae and is necessary for the de novo induction of a second prion, [PSI(+)]. The function of Rnq1, however, is little understood. The limited availability of defective rnq1 alleles impedes the study of its structure-function relationship by genetic analysis. In this study, we isolated rnq1 mutants that are defective in the stable maintenance of the [PIN(+)] prion. Since there is no rnq1 phenotype available that is applicable to a direct selection or screening for loss-of-function rnq1 mutants, we took advantage of a prion inhibitory agent, Rnq1Δ100, to develop a color-based genetic screen. Rnq1Δ100 eliminates the [PSI(+)] prion in the [PIN(+)] state but not in the [pin(−)] state. This allows us to find loss-of-[PIN(+)] rnq1 mutants as white [PSI(+)] colonies. Nine rnq1 mutants with single-amino-acid substitutions were defined. These mutations impaired the stable maintenance of [PIN(+)] and, as a consequence, were also partially defective in the de novo induction of [PSI(+)]. Interestingly, eight of the nine alleles were mapped to the N-terminal region of Rnq1, which is known as the non-prion domain preceding the asparagine and glutamine rich prion domain of Rnq1. Notably, overexpression of these rnq1 mutant proteins restored [PIN(+)] prion activity, suggesting that each of the rnq1 mutants was not completely inactive. These findings indicate that the N-terminal non-prion domain of Rnq1 harbors a potent activity to regulate the maintenance of the [PIN(+)] prion.